The Influence of Halal Certification, Halal Awareness and Product Quality on Buying Interest in Halal Cosmetic Products for the Local Brand Make Over - Ayunda, Sucia Eka; Harsoyo, Titik Desi (Jurnal Ilmiah Manajemen Kesatuan, 2024)
Analyzing the influence of halal certification, halal awareness and product quality on interest in purchasing halal cosmetic products from the local brand Make Over as the aim of this research. The sample used was 100 Muslim female consumers who were aware of Make Over cosmetics but had never purchased or used the brand. The survey method using a questionnaire is the technique used to collect data for this research. The instrument test results prove that all the data in this study are valid and reliable. From the results of the classical assumption test, it is shown that the data in this study is normally distributed, does not contain multicollinearity and heteroscedasticity. The research results show: (1) halal certification has no effect on interest in buying halal cosmetic products from the local brand Make Over (2) halal awareness has a positive and significant effect on interest in buying halal cosmetic products from the local brand Make Over (3) product quality has a positive and significant effect on interested in buying halal cosmetic products from the local brand Make Over. The resulting theoretical implications support and provide evidence for previous findings, namely the successful testing of the influence of halal awareness and product quality on purchasing interest as well as providing support for previous research regarding the absence of the influence of halal certification on purchasing interest. The managerial implication is provide input to Make Over's marketing department to demonstrate halal certification so that it can have an influence on purchasing interest.